Archaeological heritage policies and management structures : proceedings of the XVII UISPP World Congress (1-7 September 2014, Burgos, Spain). - Robrahn-González, Erika M. (Archaeopress Publishing Ltd, 2017)
This volume presents proceedings from sessions A15a, A15b, A15c of the XVII UISPP World Congress (1-7 September 2014, Burgos, Spain). Collectively this volume presents perspectives of archaeological heritage management in various countries and continents.